Co-movements between Islamic and conventional stock markets: an empirical evidence - Sahabuddin, Mohammad; Muhammad, Junaina; Yahya, Mohamed Hisham; Mohammed Shah, Sabarina (Penerbit Universiti Kebangsaan Malaysia, 2020)
This paper examines the co-movement between the Islamic (Shariah compliant) and conventional stock indices. Using data from Bangladesh and Malaysia from 25 January, 2011 to 31 May, 2018, the study employs the co-integration approach and Vector Error Correction Model (VECM). The results reveal that there is a significant co-integration relationship among the variables. The analysis of the Variance Decomposition indicates that there are weak (strong) influences for predating the forecast errors of the respective indexes in the short run and long run while the impulse response function (IRF) shows negatively (positively) to the shocks with each other in the Islamic and conventional stock indexes. These findings provide useful insights to investors and policy makers in reducing risks and achieving the optimum level of return.